Plasma methotrexate concentrations in urothelial cancer chemotherapy - Kitamura, Y (Hinyokika kiyo. Acta urologica Japonica, 1990)
The plasma methotrexate (MTX) concentration was measured during 50 courses of chemotherapy on 26 urothelial cancer patients. A dose of 300 mg/body MTX was infused within 2 hours and plasma concentrations were measured at the scheduled times. Plasma level at the end of infusion was (2.3 +/- 0.8) x 10(-5) M/L, (2.9 +/- 1.9) x 10(-5) M/L at the 6th-hour, and (1.9 +/- 1.8) x 10(-7) M/L at the 24th-hour after the infusion. The plasma MTX concentration values were inversely correlated with creatinin clearance. In 6 cases of Kock pouch bladder, clean intermittent self catheterization of urine caused no meaningful increase of MTX